2022
DOI: 10.3390/app12031280
|View full text |Cite
|
Sign up to set email alerts
|

Thinning Methods to Regulate Sweet Cherry Crops—A Review

Abstract: In perennial fruit crops, bearing can be influenced by various factors, including environmental conditions, germplasm, rootstocks, and cultivation methods. Cherries, one of the most important and popular fruit species from the temperate climate zone, achieve high prices on the market. New agricultural technologies and environmental factors force a change in the approach to cherry cultivation. Old-type cherry orchards, with their high demand for water, nutrients, and manual work, are replaced by orchards of sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…However, cherry trees often do not drop flowers, and thus require additional resources and mechanical and hormonal thinning to protect the yield and quality. In the past, the requirement for thinning during cherry production was rare; however, due to the introduction of dwarfing rootstock (see Section 7.4), thinning has become necessary to avoid excessive flowering [173]. Thinning can be carried out via large-scale pruning, mechanical hand removal of flowers or chemical thinning.…”
Section: Thinning and The Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cherry trees often do not drop flowers, and thus require additional resources and mechanical and hormonal thinning to protect the yield and quality. In the past, the requirement for thinning during cherry production was rare; however, due to the introduction of dwarfing rootstock (see Section 7.4), thinning has become necessary to avoid excessive flowering [173]. Thinning can be carried out via large-scale pruning, mechanical hand removal of flowers or chemical thinning.…”
Section: Thinning and The Environmentmentioning
confidence: 99%
“…Thinning can be carried out via large-scale pruning, mechanical hand removal of flowers or chemical thinning. These different methods have recently been reviewed by Rutkowski and Lysiak [173]. Thinning, however, comes with inherent risks.…”
Section: Thinning and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene released from CEPA inside the cultivation container was used in the present study, and it seems that at 100 μL L –1 ethylene, side effects of CEPA breakdown products appeared, as petiole elongation was not further stimulated and leaf petiole water content decreased independently on ethylene binding to the receptors, as MCP did not reverse this response ( Figure 6 B). CEPA-containing products have indeed been used in agricultural practice, both as defoliants and desiccants [ 63 , 64 ]. Upon breakdown, CEPA also releases phosphoric acid and Cl – [ 65 ], which could have an additional effect at a high concentration of CEPA.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest SSC in our study was found in the year of the most abundant yield. High crop loads may have certain negative effects on fruit SSCs [ 47 ], and reducing the crop load results in an increase in SSC [ 48 ].…”
Section: Discussionmentioning
confidence: 99%